Capacidad organizacional y su relación en la satisfacción laboral de los trabajadores del PEHCBM, periodo 2014 - García Torres, Cinthya Steffany (2015)
This research titled: ORGANIZATIONAL CAPACITY AND THEIR RELATIONSHIP IN THE JOB SATISFACTION OF WORKERS PEHCBM, PERIOD 2014, it aims to assess the organizational capacity and the relationship with job satisfaction of employees of the Special Huallaga Central Project and Bajo Mayo in the 2014 period. The research worked with a type of non-experimental research, with a level of qualitative research, with a population sample comprised of workers who are working for a period of over five years, ie 51 employees of the Special Project Huallaga Central and Bajo May, using the survey instrument technique and the use of a questionnaire. In conducting the investigation it was found that the organizational capacity of the staff of the Special Huallaga Central Project and Bajo Mayo, period 2014 is at a very low level (49%) and job satisfaction of workers is at a level very dissatisfied (50.98%). Thereby giving the acceptance of alternative and rejected the null hypothesis, where it is hypothesized that organizational capacity is weak, and is related to high fashion